2014
DOI: 10.1016/j.compag.2014.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge discovery and Leaf Spot dynamics of groundnut crop through wireless sensor network and data mining techniques

Abstract: Data driven precision agriculture aspects, particularly the dynamic disease management, require dynamic crop-weatherenvironment data at micro level. An experiment was conducted during four consecutive seasons (2009 Kharif, 2009-10 Rabi, 2010 Kharif and 2010-11 Rabi) in a semi-arid tropic region of India to understand the crop-weather-environmentdisease relations using wireless sensory and field-level surveillance data on the groundnut crop for Leaf Spot (LS) disease, which is economically important yet more pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 19 publications
0
14
0
4
Order By: Relevance
“…Let ℎ denote the throughput. So, formula (2) gives the data selection model based on service opportunistic driven. Here, service request launched the service opportunistic driven in accordance with the probability.…”
Section: Data Selection Mechanism Driven By Mobile Internet Servicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Let ℎ denote the throughput. So, formula (2) gives the data selection model based on service opportunistic driven. Here, service request launched the service opportunistic driven in accordance with the probability.…”
Section: Data Selection Mechanism Driven By Mobile Internet Servicesmentioning
confidence: 99%
“…The cloud platform has high performance of data management and efficient data mining [1], which has been widely applied in various fields, such as knowledge discovery and Leaf Spot dynamics [2], and ERP applications [3]. So, the cloud platform [4,5] has played an important role for quality of service guarantee and data mining of mobile Internet.…”
Section: Introductionmentioning
confidence: 99%
“…Site-specific management of crop pests, as well as management of agricultural inputs and irrigation, requires accurate estimates of crop status and agro-meteorological conditions and characterizations of their intra-plot variability [42]. Several authors are unanimous on the fact that management of diseases and pests, characterized by a high spatial and temporal dynamics, requires specific agro-meteorological information at the field and microclimate scales [67][68][69]. Matese et al [70], for example, have shown that the microclimate of vineyards is characterized by high spatial variability (intravignoble and intervignoble) meaning that measurements from meteorological stations located outside of these vineyards do not effectively reflect the microclimate conditions occurring there.…”
Section: Introductionmentioning
confidence: 99%
“…Tripathy et al present knowledge discovery and leaf spot dynamics of groundnut crop by wireless sensor network and data mining techniques. The useful information, knowledge or relations from all kinds of data mining techniques would be helpful to analyze and understand leaf spot disease infection [25]. In order to protect sensor nodes from malicious attacks, Huang et al proposed a new intrusion detection method.…”
Section: Introductionmentioning
confidence: 99%